Economic and environmental characteristics of global cellular telephone remanufacturing - Skerlos, S.J.; Morrow, W.R.; Kuei-yuan Chan; Fu Zhao; Hula, A.; Seliger, G.; Basdere, B.; Prasitnarit, A. (IEEE International Symposium on Electronics and the Environment, 2003, 2003)
This paper investigates the state-of-the art in remanufacturing of cellular telephones and discusses economic and environmental issues relative to primary manufacturing. Characteristics of developed countries versus lesser developed countries are explicitly considered in the remanufacturing enterprise, and the corresponding impacts of introducing remanufactured cellular telephones to such markets is discussed. It is shown that while remanufacturing as a process carries a much lower environmental burden than primary manufacturing, the remanufacturing enterprise will likely add to the net environmental burden of the telecom industry, rather than reduce it. The extent of this impact depends on situational issues such as transportation and energy grid technology. The value of expanding the remanufacturing enterprise is also discussed in the context of sustainable development.